Unleashing The Power of CML: The Journey to EKSA Award! - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2024)
21 February 2024 - The Public Sector Conducive Ecosystem, better known as EKSA, is a rebranding exercise of Public Sector 5S practice. The initiative aims to strengthen the organisational culture of high performance and innovation among public sector agencies by providing a conducive environment, work culture, and positive values for public servants. In the spirit of EKSA, the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is also implementing this practice to meet its objectives